Neuroimaging adolescents with depression in a middle-income country: feasibility of an fMRI protocol and preliminary results - Battel, Lucas (Braz J Psychiatry, 2019)
OBJECTIVE: To test the feasibility and to present preliminary results of a neuroimaging protocol to evaluate adolescent depression in a middle-income setting. METHODS: We assessed psychotropic medication-free adolescents (age range 14-16 years) with a diagnosis of major depressive disorder (MDD). Participants underwent a comprehensive clinical evaluation and both structural and functional magnetic resonance imaging (fMRI). In this pilot study, a preliminary single-group analysis of resting-state fMRI (rs-fMRI) data was performed, with a focus on the default mode network (DMN), cognitive control network (CCN), and salience network (SN). RESULTS: The sample included 29 adolescents with MDD (mean age 16.01, SD 0.78) who completed the protocol. Only two participants were excluded due to MRI quality issues (head movement), and were not included in the analyses. The scans showed significant connectivity between the medial prefrontal cortex and posterior cingulate cortex (DMN), the ACC and anterior insula (SN), and the lateral prefrontal cortex and dorsal parietal cortex (CCN). CONCLUSION: We demonstrated the feasibility of implementing a complex neuroimaging protocol in a middle-income country. Further, our preliminary rs-fMRI data revealed patterns of resting-state connectivity consistent with prior research performed in adolescents from high-income countries.